2009
DOI: 10.5001/omj.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Calcium Correction during Normal Pregnancy at Third Trimester in Mosul

Abstract: In healthy pregnant women even during limited sun exposure time in winter, there was no need for calcium supplementation in spite of the continuous and progressive reduction of serum measured total calcium during the second and third trimesters due to dilutional hypoalbuminemia. During pregnancy, measured calcium is parallel to both corrected and ionized calcium and since there was no significant difference between measured and corrected calcium, therefore, measured calcium is a useful test in assessing calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…In this study, measured total calcium was significantly reduced in the second trimester (9.72 ± 2.04) in comparison to first trimester (10.88 ± 1.97). The results of the study are similar to the results obtained by Hanna B. et al who reported reduced total calcium levels in second and third trimester compared to first trimester [40]. The probable reasons for reduced calcium levels in second trimester is due to increased nutritional demands of the growing fetus, expanded intravascular space, reduced albumin concentration, serum PTH is lower by 50% in pregnancy and increased excretion of calcium as a result of increased GFR [41].…”
Section: Discussionsupporting
confidence: 89%
“…In this study, measured total calcium was significantly reduced in the second trimester (9.72 ± 2.04) in comparison to first trimester (10.88 ± 1.97). The results of the study are similar to the results obtained by Hanna B. et al who reported reduced total calcium levels in second and third trimester compared to first trimester [40]. The probable reasons for reduced calcium levels in second trimester is due to increased nutritional demands of the growing fetus, expanded intravascular space, reduced albumin concentration, serum PTH is lower by 50% in pregnancy and increased excretion of calcium as a result of increased GFR [41].…”
Section: Discussionsupporting
confidence: 89%
“…We observed a non-significant reduction in total serum calcium levels during normal pregnancy ( p = 0.779). This observation is supported by those of Standley et al, [ 22 ] and Olatunbosum et al, [ 39 ] but contrast those of Bassam Hanna [ 40 ] and Sultana et al, [ 41 ]. Studies by Bassam Hanna and Sultana et al, argued that the low serum total calcium observed in late normal pregnancy was due to increased foetal demand and physiological haemodilution secondary to increased intravascular volume as a result of significantly reduced serum albumin levels (which is the main calcium binding plasma protein) [ 40 ], [ 41 ].…”
Section: Discussionsupporting
confidence: 71%
“…Levels of iPTH are regulated mainly by levels of ionized calcium, and not by 25(OH)D levels[ 78 ]. The total serum calcium decreases in late pregnancy due to dilutional hypoalbuminemia, but there was no significant difference in both serum ionized calcium and corrected calcium during pregnancy[ 79 ]. Nonetheless, ionized calcium or albumin-corrected serum calcium should be measured for accurate level of calcium during the pregnant state[ 80 ].…”
Section: Discussionmentioning
confidence: 99%